A Simple Route to Strong Carbon‐13 NMR Signals Detectable for Several Minutes. Issue 44 (19th July 2017) - Roy, Soumya S.; Norcott, Philip; Rayner, Peter J.; Green, Gary G. R.; Duckett, Simon B.
Abstract: Nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI) suffer from low sensitivity and limited nuclear spin memory lifetimes. Although hyperpolarization techniques increase sensitivity, there is also a desire to increase relaxation times to expand the range of applications addressable by these methods. Here, we demonstrate a route to create hyperpolarized magnetization in 13 C nuclear spin pairs that last much longer than normal lifetimes by storage in a singlet state. By combining molecular design and low‐field storage with para ‐hydrogen derived hyperpolarization, we achieve more than three orders of signal amplification relative to equilibrium Zeeman polarization and an order of magnitude extension in state lifetime. These studies use a range of specifically synthesized pyridazine derivatives and dimethyl p ‐tolyl phenyl pyridazine is the most successful, achieving a lifetime of about 190 s in low‐field, which leads to a 13 C‐signal that is visible for 10 minutes. Abstract : Only time will tell : A fast and cost‐effective method to increase carbon‐13 NMR sensitivity by three orders of magnitude is detailed for a series of pyridazine derivatives. When the resulting polarization is stored as long‐lived singlet order, the resulting hyperpolarized 13 C NMR signals remain detectable for up to 10 minutes.